2015
DOI: 10.1016/j.lungcan.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral CD10 expression correlates with high-grade histology and increases risk of recurrence in patients with stage I lung adenocarcinoma

Abstract: Objective CD10 (neutral endopeptidase) is expressed in various normal and tumor cells, and its biological function can be controlled through enzymatic activity and signaling pathways. We investigated whether CD10 expression predicted disease recurrence and whether it correlated with histologic subtypes of stage I lung adenocarcinoma. Material and Methods We reviewed tumor slides of resected pathologic stage I lung adenocarcinomas (1995–2009). Tumors were classified according to the IASLC/ATS/ERS classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…Apart from the aforementioned reports, there are other biomarkers associated with MPP that have been reported, such as higher expression of cytoplasmic maspin, 64 Notch-1, 65 and tumoral CD10. 66 However, there is a lack of additional literature to validate the correlations between these biomarkers and the presence of MPP, so we will not clarify them in detail here. MPPAC also has molecular markers specifically related to ADC, for example, TTF-1.…”
Section: Molecular Featuresmentioning
confidence: 99%
“…Apart from the aforementioned reports, there are other biomarkers associated with MPP that have been reported, such as higher expression of cytoplasmic maspin, 64 Notch-1, 65 and tumoral CD10. 66 However, there is a lack of additional literature to validate the correlations between these biomarkers and the presence of MPP, so we will not clarify them in detail here. MPPAC also has molecular markers specifically related to ADC, for example, TTF-1.…”
Section: Molecular Featuresmentioning
confidence: 99%
“…Several reports have indicated that many human epithelial tumours express stromal CD10 . These reports demonstrated that a high level of CD10 expression in neoplasms tended to be associated with poor clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Both neoplastic cells (mostly of epithelial cell origin) and non‐neoplastic intratumoral stromal cells express CD10. Although non‐neoplastic cells from some organs express CD10, and the tumours arising from these organs may also express CD10, it is notable that CD10 can also be expressed in neoplastic cells arising from organs with normal cells that do not express CD10 …”
Section: Introductionmentioning
confidence: 99%
“…Second, some differentially expressed proteins that did not overlap in the serum and cell lines have great diagnostic potential. Of the 50 differentially expressed proteins in the advanced NSCLC group versus the early NSCLC group, neprilysin, CD44, and basigin were obviously increased in patients with advanced NSCLC. These proteins are widely reported to be closely associated with cancer progression and metastasis in cell line and tissues.…”
Section: Discussionmentioning
confidence: 94%